Rhetorics of Moderation in Digital Da’wah: Framing Islamic Values on YouTube - Gina Sonya Pane; Juni Wati Sri Rizki; Pahri Siregar (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the rhetorical construction of religious moderation in the Log In program on Deddy Corbuzier’s YouTube channel. Amidst the polarization of digital religion, this research analyzes how Islamic values are framed to appeal to diverse audiences. Using a qualitative design that combines virtual ethnography and Critical Discourse Analysis (CDA), the researcher observed and transcribed 30 episodes of the program. The analysis applies Aristotelian rhetorical theory (ethos, pathos, and logos) to explore how credibility, emotional appeal, and logical argumentation are articulated through language style, humor, and narrative strategies. The findings reveal that Habib Husein integrates these rhetorical elements in a balanced manner, producing religious messages that are rational, engaging, and socially relevant. His rhetoric reflects an adaptive style that aligns with the interactive and monetized nature of YouTube. Beyond descriptive insights, this study contributes theoretically by demonstrating how Aristotelian rhetoric operates within the political economy of digital media, where religious messages function simultaneously as spiritual guidance and commodified content.